10-year trend analysis of in-hospital cardiac arrest: 2008–2017 United State hospitalizations. (25th November 2020) - Wu, L; Huang Lucus, C; Yang, Y.F; Liu, B.Q; Guo, Y
Abstract: Introduction: In-hospital cardiac arrest (IHCA) survival trends have not been well reported in recent years. Whether the implementation of the new 2015 AHA guideline affects the survival of IHCA is largely unknown. Our study aims to provide an updated analysis of the trends of IHCA among the hospitals in the United States Method: Using United States National Inpatient Sample Database 2008–2017, the cohort was generated with patients age above 18 who received Cardiopulmonary resuscitation during Hospitalization. Hospitalization with a principle diagnosis of cardiac arrest or ventricular fibrillation/ventricular tachycardia were excluded as outside hospital cardiac arrest. Demographic features, baseline characteristic as well as hospital outcomes were described. Trend analysis was performed using a multivariate model adjusted for age, sex, and comorbidities score. Results: From 2008 to 2017, the cases of In-hospital cardiac arrest (IHCA) has steadily increased from 96, 771 to 106, 320. This trend was accompanied by a decline in age from (67.48±0.30 to 65.78±0.13, Ptrend <0.001) but increase in comorbidity score (from 2.44±0.27 to 3.47±0.21, Ptrend <0.001). It is noted that the mortality rate has been steadily declining since 2008 (from 74.01% to 68.68%, Ptrend <0.001)), although no significant changes before or after 2015 were noted (from 68.90 to 68.68, P>0.05). Length of stay has decreased from an average of 9.06± days to 8.76±0.13 days at the cost of increased health care costs (from 30.78 to 37.40 thousand dollar P<0.001 adjusted for inflation rate). Conclusion: The survival rate of In-hospital cardiac arrest has increased from 2008 to 2017 despite increased comorbidity burden. The length of stays has decreased at the cost of an increase in health costs. Funding Acknowledgement: Type of funding source: None